INTERPERSONAL COMMUNICATION BETWEEN PRODUCER AND PRODUCTION TEAM OF THE CELEBRITY TOP 10 PROGRAM AT MNC LIFESTYLE & FASHION - Ahmad Nasher; Fika Rizky Rahmani; Najibah Malika (Universitas Gunadarma, 2023)
Interpersonal communication is a type of communication that is considered the most effective in changing attitudes and behavior in the form of dialogue. This research aims to understand interpersonal communication between the producers and the production team of the Celebrity Top 10 program at MNC Lifestyle & Fashion. The theory used in this research is symbolic interaction theory to see how different symbols relate to the study of concepts, themes, and their roles. The method used is a qualitative method with a constructivist paradigm. Data collection techniques are carried out using interviews, observation, and documentation. This research shows that communication activities between the producer and the production team of the Celebrity Top 10 Program, which consists of 5 people, namely the Producer, Senior Production Assistant, Production Assistant Intern, Creative, and Editor, have gone well. The most common method producers and production teams use to communicate with each other is to hold small meetings to learn about the topics that will be covered on the broadcast. The production team also held meetings outside office hours to see the team's progress in implementing the Celebrity Top 10 Program and providing solutions and motivation to all team members. Several obstacles were felt, including differences in views, difficulties understanding the material, and limited equipment. That is why the alternative is to actively exchange opinions, utilize individual expertise, and take turns using equipment.